EP-86 Preventable errors in hand surgery: analysis of data from NHS England. (9th August 2022) - Hafez, Ahmed; Omar, Islam; Ang, Andrew; Mahawar, Kamal
Abstract: Background: Avoidable medical errors and never events represent a significant problem with negative consequences on the patient, the healthcare professionals, and the healthcare facilities. Hand surgery is a unique multidisciplinary speciality in which orthopaedics, plastic and general surgery are usually involved in the care of their patients, which makes this speciality prone to medical errors. The study highlights these preventable errors in hand surgery in NHS England. Methods: We analysed hand surgery-related preventable medical errors published by the NHS England during the last ten years from 2012 till July 2021. Results: Out of 3742 never events during the review period, only 50 never events related to hand surgery were found, representing (1.3%). The majority were under wrong-site surgery category 30 (60%), which included 17 (57%) wrong finger or digit surgery followed by five wrong digit or thumb injections, three wrong K wire placement, and three scaphoid bones were mistakenly removed during trapeziectomy. The second most common category was wrong incision 15 (30%), with 13 wrong finger incisions, two wrong carpal tunnel incisions for trigger finger release. Four patients had wrong procedures, including CTR rather than trigger finger or Dequervain release or an unnecessary carpal tunnel release in addition to one wrong hand tendon transfer. Lastly, only one patient had a wrong injection for carpal tunnel that was intended for another patient. Conclusions: Hand surgery-related medical errors represent 1.3% of the whole Never Events reported. Awareness of these incidents will help prevent their occurrence in the future.